Between‐individual variation drives the seasonal dynamics in the trophic niche of a Neotropical marsupial. (28th November 2012) - Pires, Mathias M.; Martins, Eduardo G.; Araújo, Márcio S.; dos, Sérgio F.
Abstract The dynamics of population niches result from the variation in resource use within individuals and also from the variation between individuals. The prevalence of one mechanism or the other leads to competing hypotheses about the major mechanisms underlying the empirical observations of the contraction/expansion dynamics of the trophic niche in natural populations. In this study, we investigated how within‐ and between‐individual variation in resource use shapes the food niche dynamics of the woolly mouse opossum, Marmosa paraguayana (Didelphimorphia: Didelphidae), in a remnant of the highly seasonal Cerrado in south‐eastern Brazil. To do so, we analysed the faecal samples of live‐trapped individuals to determine their diets within the wet and dry seasons. In addition to a seasonal shift in the composition of the diet, the population trophic niche was significantly wider during the dry season than the wet season. This expansion resulted from larger between‐individual variation in the dry season that was not related to sex preferences, whereas the individual niche widths did not significantly increase from the wet to the dry seasons. Our findings add to the growing list of animal populations that show individual‐level variation in resource use. Furthermore, these results represent a pattern of individual‐level response to seasonal changes that is different from patterns reported for other organisms. We suggest that a pathway to build more realistic foraging models and produce more accurate predictions on population and community dynamics is to consider between‐individual variation and short‐term niche dynamics.